Second Time University Program as a Public Policy: Contributions and Limitations to Physical Leisure Activities and Health Promotion - Alex Caiçara de Albuquerque; Junior Vagner Pereira da Silva (Sports)
The Second Time University Program is a federal government policy instituted in 2009. Given its importance, this study aimed to analyze the program’s contributions and limitations in promoting leisure-time physical activity and student health. The study is a retrospective longitudinal, qualitative–quantitative, exploratory and documentary study, analyzing the guidelines and public notices between 2009 and 2023. The program is predominantly focused on integral development, with the inclusion of objectives aimed at health promotion, relating leisure-time physical activities to a physically active lifestyle and a reduction in sedentary lifestyles in 2020. Its scope is low and selective, with a presence in only 47.82% of universities. Continuity is also low, with the majority of universities only being covered by the program in one call for proposals. In conclusion, although it promotes leisure-time physical activity and holistic health promotion, the public policy is limited and discontinuous.